Toxic and essential metals: metabolic interactions with the gut microbiota and health implications - Zhu, Qinheng; Chen, Boyan; Zhang, Fu; Zhang, Baodan; Guo, Yujie; Pang, Mengtao; Huang, Liang; Wang, Tianjiao (Frontiers in Nutrition, 2024)
Human exposure to heavy metals, which encompasses both essential and toxic varieties, is widespread. The intestine functions as a critical organ for absorption and metabolism of heavy metals. Gut microbiota plays a crucial role in heavy metal absorption, metabolism, and related processes. Toxic heavy metals (THMs), such as arsenic (As), mercury (Hg), lead (Pb), and cadmium (Cd), can cause damage to multiple organs even at low levels of exposure, and it is crucial to emphasize their potential high toxicity. Nevertheless, certain essential trace elements, including iron (Fe), copper (Cu), and manganese (Mn), play vital roles in the biochemical and physiological functions of organisms at low concentrations but can exert toxic effects on the gut microbiota at higher levels. Some potentially essential micronutrients, such as chromium (Cr), silicon (Si), and nickel (Ni), which were considered to be intermediate in terms of their essentiality and toxicity, had different effects on the gut microbiota and their metabolites. Bidirectional relationships between heavy metals and gut microbiota have been found. Heavy metal exposure disrupts gut microbiota and influences its metabolism and physiological functions, potentially contributing to metabolic and other disorders. Furthermore, gut microbiota influences the absorption and metabolism of heavy metals by serving as a physical barrier against heavy metal absorption and modulating the pH, oxidative balance, and concentrations of detoxification enzymes or proteins involved in heavy metal metabolism. The interactions between heavy metals and gut microbiota might be positive or negative according to different valence states, concentrations, and forms of the same heavy metal. This paper reviews the metabolic interactions of 10 common heavy metals with the gut microbiota and their health implications. This collated information could provide novel insights into the disruption of the intestinal microbiota caused by heavy metals as a potential contributing factor to human diseases.